Titania Nanosheets Generates Peroxynitrite for S-Nitrosylation and Enhanced p53 Function in Lung Cancer Cells - Rapeepun Soonnarong; Sucharat Tungsukruthai; Bodee Nutho; Thanyada Rungrotmongkol; Chanida Vinayanuwattikun; Tosapol Maluangnont; pithi chanvorachote (My University, 2021)
Abstract Background: Metal oxide nanomaterials are increasingly being exploited in cancer therapy thanks to their unique properties, which can enhance the efficacy of current cancer therapies. However, the nanotoxicity and mechanism of Ti 0.8 O 2 nanosheets for specific site-targeting strategies in NSCLC have not yet been investigated. Methods: The effects of Ti 0.8 O 2 nanosheets on cytotoxicity in NSCLC cells and normal cells were examined. The apoptosis characteristics, including condensed and fragmented nuclei, as assessed by positive staining with annexin V. The cellular uptake of the nanosheets and the induction of stress fiber were assessed via transmission electron microscopy (TEM) and scanning electron microscopy (SEM) analyses, respectively. We also evaluated the expression of protein in death mechanism to identify the molecular mechanisms behind the toxicity of these cells. We investigated the relationship between S -nitrosylation and the increase in p53 stability by molecular dynamics. Results: Ti 0.8 O 2 nanosheets caused cytotoxicity in several lung cancer cells, but not in normal cells. The nanosheets could enter lung cancer cells and exert an apoptosis induction. Results for protein analysis further indicated the activation of p53, increased Bax, decreased Bcl-2 and Mcl-1, and activation of caspase-3. The nanosheets also exhibited a substantial apoptosis effect in drug-resistant metastatic primary lung cancer cells, and it was found that the potency of the nanosheets was dramatically higher than that of cisplatin and etoposide. In terms of their mechanism of action, we found that the mode of apoptosis induction was through the generation of cellular ONOO − mediated the S -nitrosylation of p53 at C182. Molecular dynamics analysis further showed that the S -nitrosylation of one C182 stabilized the p53 dimer. Consequently, this nitrosylation of the protein led to an upregulation of p53 through its stabilization. Conclusions: Taking all the evidence together, we provided information on the apoptosis induction effect of the nanosheets through a molecular mechanism involving reactive nitrogen species, which affects the protein stability; thus emphasizing the novel mechanism of action of nanomaterials for cancer therapy.
Keywords: Nanotoxicology; Advanced Nanomaterials in Catalysis